KOMPETENSI PEDAGOGIK GURU MATEMATIKA DARI PERSEPSI SISWA: SEBUAH SURVEI PADA SEKOLAH MENENGAH DI SULAWESI BARAT: KOMPETENSI PEDAGOGIK GURU MATEMATIKA DARI PERSEPSI SISWA: SEBUAH SURVEI PADA SEKOLAH MENENGAH DI SULAWESI BARAT - Fadhil Zil Ikram; Anaguna, Nursyam; Aprisal; Rosidah; Machmud, Muhammad Takwin (MaPan : Jurnal Matematika dan Pembelajaran, 2024)
The results of the PISA 2022 assessment, along with preliminary studies conducted in West Sulawesi, indicate that students' proficiency in mathematics remains significantly below expectations. One of the factors contributing to students' limited proficiency in mathematics is associated with the pedagogical competence of their instructors. This study employs a quantitative research design utilizing a survey instrument to describe the level of pedagogical competence of mathematics teachers in secondary schools in West Sulawesi, based on student perceptions, and to identify the specific competencies that require development. The population of this study was all secondary school students in West Sulawesi, with a sample size of 1.051 senior secondary school students and 988 junior secondary school students. The analysis employed was descriptive statistical analysis using a stratified random sampling method. The findings indicate that a considerable proportion of mathematics teachers at both the junior high school and senior high school levels exhibit inadequate proficiency. The pedagogical competence of teachers is still lacking in several key areas, which require further development: (1) The skill to comprehend student characteristics; (2) The capability to select materials that are aligned with the learning experience and learning objectives; (3) The ability to select media and learning resources that are suitable for student needs; (4) The skill to make transactional decisions in response to situations that arise in the classroom; (5) The ability to integrate and utilize technology in learning; (6) The skill to communicate effectively; and (7) The skill to evaluate learning. The results of this study can be used as a guideline for the government, experts, and policymakers to overcome the problem of teacher competency development. In addition, the results can be used to design and determine the direction of policies and programs for developing mathematics teacher pedagogical competencies in West Sulawesi.